Automação de um moedor de grãos de pimenta - Smokovicz, Fernando Schmitz (2013)
In this work is shown the development of an automation for a manually grinding peppercorns equipment, located in a local market in Araucaria, with the goal of making automated equipment to replace human labor in practice and through the program developed by GRAFCET ensure amount requested by the client. Through literature searches, are understood key parts to assemble structural and programming it. For the first part of automation is becoming automated equipment was purchased grains manually grinder, then gave the start of assembly of the parts that make automatic, after which the program was developed to operate in the same automatic language programming was used - ladder and Grafcet - thus facilitating the understanding of the program for future users who wish to understand, modify and even improve. The tests were performed in the equipment, making the grinding according to the program established in the panel and optional equipment. Thus bringing the benefit of removing human labor and ensure the amount requested.